The Division of Spousal Roles in Rural Communities:A Critical Analysis of Gender Bias in Islamic Law - M. Syahrur Romadhon (International Journal of Sharia and Law, 2026)
This study aims to uncover gender-biased behavior within households in remote areas, while also exploring what Islam truly teaches about the role of a wife. Women living in rural and isolated communities frequently face gender discrimination they tend to be treated as second-class citizens whose sole purpose is managing domestic affairs at home. This kind of treatment gives rise to a patriarchal culture in which husbands dominate and maintain full control over the household, ultimately leading to gender disparity and, further down the line, deeply ingrained gender-biased behavior. This research adopts a normative-empirical approach, drawing on both primary and secondary data sources. The primary data was collected directly from the field specifically from a village in Musi Rawas Regency, Bengkulu while the secondary data was gathered from various books and academic journals. The findings reveal that women in these remote areas experience numerous forms of gender bias, particularly when it comes to the division of roles within the household. Wives are largely confined to childcare and domestic chores, with little to no involvement in decision-making, as that authority is considered the husband's exclusive right. This reflects a clear pattern of marginalization wives are reduced to second-class status and subjected to subordination, denied equal standing with their husbands in both public and domestic spheres. Furthermore, some women are burdened with a double load: they are expected to contribute financially to the family while still shouldering all household responsibilities on their own, without any help from their husbands not even when it comes to raising the children, since the husband sees his only duty as earning a living. This kind of dynamic stands in stark contrast to Islamic teachings, which call for the principle of mu'asyarah bil ma'ruf treating one's spouse with kindness and fairness as well as the principle of mubadalah, which emphasizes cooperation and mutual support, where both husband and wife work together and help each other in fulfilling their respective roles and responsibilities.